The Role of the Jewish House of Representatives inside and Outside Britain from 1837 to 1841 - Fadhila Hussein Radhi; Dr. Naeem Kareem Ojeemy (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to shed light on the role of the Jewish House of Representatives inside and outside Britain for the period from 1837 to 1841. And to indicate the most important activities of the Jewish's Parliament during that period to reduce the obstacles that faced the Jewish minority in Britain, and the most prominent Jewish personalities who actively participated in strengthening the Jewish presence there. This research reached many results, the most important of which are that Moses Montefiore played a crucial role in the Jewish House of Representatives, which led to success in its mission for which it was established, it was able to serve the Jews inside and outside Britain, and raise the status of Jews in it.